Agilent Technologies Case Study - Basic Instrument Division - Sim, Ooi Aik (2009)
Agilent Technologies, one of the world's premier test measurement service providers is also facing fierce competition in low cost test equipment market. In the past, Agilent Technologies did not focus in low cost instrument market. However, the changes of the external environmental have altered the industry playing ground. After realizing the opportunities from the low cost market, Agilent decided to setup a new division to focus on the market segment and to gain back the market share.